2022
DOI: 10.1371/journal.pone.0278552
|View full text |Cite
|
Sign up to set email alerts
|

The influence of race tactics for performance in the heats of an international sprint cross-country skiing competition

Abstract: The purpose of this study was to examine the influence of race tactics for performance in the heats of an international sprint cross-country (XC) skiing competition in the classical style. Thirty elite male XC skiers (age: 24±3 years, sprint International Ski Federation [FIS] points: 61±27) performed a sprint time-trial (STT) followed by one to three ‘knock-out’ heats on a 1.7 km racecourse. An integrated GNSS/IMU system was used to determine position, sub-technique distribution and kinematics. Positioning was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 56 publications
5
3
0
Order By: Relevance
“…Specifically, participants exhibited higher speeds in the first uphill section (S1), but lower speeds in S2–4, and particularly S3 (uphill), during TT compared to the heats. This finding aligns with a recent study by Haugnes et al ( 2022 ) who investigated a “real-world” classical sprint competition among elite XC skiers, highlighting considerable differences in the speed profiles (i.e., pacing strategies) adopted in the individual TT compared to the subsequent heats. These differences can be attributed to lower speeds and greater emphasis on positioning in the initial part of the heats, followed by higher speeds to outpace competitors in the latter part.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Specifically, participants exhibited higher speeds in the first uphill section (S1), but lower speeds in S2–4, and particularly S3 (uphill), during TT compared to the heats. This finding aligns with a recent study by Haugnes et al ( 2022 ) who investigated a “real-world” classical sprint competition among elite XC skiers, highlighting considerable differences in the speed profiles (i.e., pacing strategies) adopted in the individual TT compared to the subsequent heats. These differences can be attributed to lower speeds and greater emphasis on positioning in the initial part of the heats, followed by higher speeds to outpace competitors in the latter part.…”
Section: Discussionsupporting
confidence: 91%
“…Participants demonstrated higher speeds in SF compared to TT, QF, and F, while F was slower than TT. These patterns align with previous research, which has indicated that heats are performed at either higher (Andersson et al 2019 ), lower (Haugnes et al 2022 ; Stöggl et al 2007 ), or the same speeds (Mikkola et al 2010 ; Vesterinen et al 2009 ) as compared to TT, depending on various factors such as tactics and the composition of study groups. Skiing in a pack during heats offers advantages such as reduced air drag and snow friction (Seeberg et al 2022a , b ), as well as potential time gains due to skiers' varying strengths on different sections of the course.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, it was shown that the strength of the correlations between intermediate rankings at given checkpoints and the final rank ranged between 0.51-0.84, with increased strength towards the finish line. In contrast, Haugnes et al [14] reported that the best performers in a male classical sprint competition awaited to position themselves at the front of the heat until approaching the final uphill, after which a clear reduction in the number of overtaking events were seen. However, whether these findings differ between the classical and skating style, racecourses, and sexes has not yet been investigated.…”
Section: Introductionmentioning
confidence: 90%
“…The four races within each sprint competition are separated by ~15 to 60-minute breaks, where the ability to recover rapidly is important for performance in the subsequent heats [1][2][3][4][5][6][7][8][9][10][11][12][13]. Moderate to large correlations between STT rank and final rank of a sprint competition have been reported [8,14], and Spencer et al [8] found a stronger correlation for men than for women, particularly evident in the skating style.…”
Section: Introductionmentioning
confidence: 99%